Cyclic behaviour of a novel steel beam-to-prefabricated CFST column connection with threaded sleeve bolts. (December 2021) - Liu, H.Q.; Liu, Y.Z.; Huo, J.S.; Zhu, D.J.
Abstract: As the conventional connection configurations of the steel beam to concrete-filled steel tubular (CFST) column are complex and unfriendly in practice, the application of the blind bolting system in steel beam-to-CFST column connection has been investigated in recent years. However, the blind bolted connections to CFST columns are generally classified as being pinned or semi-rigid and of partial strength due to the susceptibility to outward deformation of the tube wall. This paper developed a novel rigid and full-strength bolted connection of steel beam to prefabricated CFST column embedded with threaded sleeve bolts. Tests on five connection specimens are conducted to experimentally study the cyclic behaviour of the proposed sleeve bolted connections. The experimental parameters include the anchorage details of the sleeve bolt, the thickness of the end plate and level of axial load. To investigate the seismic performance of the proposed connections, the failure modes, hysteretic curves, connection rotation and ductility, stiffness and strength degradation, and energy dissipation capacity are presented and analyzed. The testing results prove that the proposed connection details have a strong influence on the cyclic behaviour and the moment-rotation behaviour of the novel connections. According to EC3, the proposed connection configurations behave as being rigid and of full-strength for non-sway frame. The component-based method is also proposed to predict the initial stiffness of the connections. The experimental and analytical results can provide a reference to promote the application of the novel sleeve bolted connections in engineering practice.